Analysis of ball interception velocity in futsal goalkeepers - Callejas-Cuervo, M.; Pineda-Rojas, J. A.; Daza-Wittinghan, W. A. (Journal of Human Sport & Exercise, 2020)
Technology constitutes a support to sports training which has an influence on the preparation of the player. This article reports on the analysis of the ball interception velocity in futsal goalkeepers. For this, a tool was created based on inertial and magnetic sensors, and a contact platform which permitted the analysis of the interception velocity. Then, a procedure was designed to execute a number of tests and a series of trials were carried out to define the factors to be evaluated. After that, tests were applied to 10 goalkeepers from the Liga Colombiana de Fútbol de Salón (Colombian Futsal League), which would permit the measurement of the study variable. The anthropometric characteristics presented by the goalkeepers selected were similar according to age, weight and body mass index, allowing homogeneity in the samples. The results showed that 50% of the interceptions to the right of the goalkeeper had a Low velocity (between 30 and 75 km/h); 40% were Medium (between 75 and 119 Km/h) and 10% were Fast (more than 119 Km/h). In addition, with respect to velocity to the left of the goalkeeper, 40% were in the Low range (between 32 and 75 Km/h) and 60% in the Medium range (75 and 119 Km/h). These results show that the goalkeepers have a better velocity performance to their right. It can be concluded that the platform is a precise and ergonomic means to measure the ball interception velocity in goalkeepers.